Immunity to Yellow Fever, Oropouche and Saint Louis viruses in a wild howler monkey - Almeida, Marco Antônio Barreto de Almeida; Cardoso, Jáder da Cruz; dos Santos, Edmilson; Romano, Alessandro Pecego Martins; Chiang, Jannifer Oliveira; Martins, Lívia Carício; Vasconcelos, Pedro Fernando da Costa; Bicca-Marques, Júlio César (Neotropical Primates, 2016)
No abstract